The privileged few - Hamilton, Clive 1953-; Hamilton, Myra (Polity, 2024)
"Clive Hamilton and Myra Hamilton show that elite privilege is not a mere by-product of wealth but an organising principle for society as a whole. They explore the practices and processes that sustain, legitimise and reproduce elite privilege, and show how we are all implicated in the system, both facilitating it and tolerating its harmful effects."
Keywords: Oberschicht; Privileg; Dominanz; Aufrechterhaltung; Soziale Ungleichheit; Elite; Gesellschaft; Ungerechtigkeit; Privilege (Social psychology); Elite (Social sciences); Entitlement attitudes; Equality; Equality / Social aspects; Social classes